Analisis Kesalahan Penulisan Kalimat Tanya Bahasa Mandarin Siswa Kelas VI SD Frater Thamrin Makassar - Thirsa Indah Permatasari; Misnawaty Usman; Arini Junaeny (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
This research is a qualitative descriptive study aimed at obtaining data about the error rate and forms of errors in writing Chinese interrogative sentences for the sixth-grade students of SD Frater Thamrin Makassar. The population in this study were all students of class VI SD Frater Thamrin Makassar with a total of 28 students. The sampling technique was carried out using total sampling, so that the entire population was used as the research sample, namely 28 people. The research data was obtained by giving a sentence writing test and a sentence composing test. Data analysis techniques using percentages. The results showed that there were 33 errors in preparing interrogative sentences with a percentage of 14.3% and errors in writing interrogative sentences as many as 39 errors with a percentage of 16.9%. The total errors in writing interrogative sentences are 72 items, including in the category of Fairly High with a percentage of 31.3%. There are three forms of errors in this study, namely the form of errors in the use of vocabulary, the form of errors in sentence structure, and the forms of errors in the use of question words. Keywords: Error Analysis, Writing, Introgative Sentences, Chinese